Limitations of point-of-care testing for low SARS CoV-2 loads: Insights for future pandemics - Ivy Rukasha (African Journal of Primary Health Care & Family Medicine)
Background: The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has seen a surge in the development of diagnostic assays. However, the performance of antigen point-of-care tests (Ag-POCTs) on samples with low viral load has not been evaluated.